2011
DOI: 10.3727/096368911x566235
|View full text |Cite
|
Sign up to set email alerts
|

Feeder-Free Derivation of Induced Pluripotent Stem Cells from Human Immature Dental Pulp Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) can be created by forcing expression of certain genes in fibroblasts or other somatic cell types, reversing them to a pluripotent state similar to that of embryonic stem cells (ESC). Here, we used human immature dental pulp stem cells (hIDPSCs) as an alternative source for creating iPSC. hIDPSCs can be easily isolated from accessible tissue of young and adult patients. hIDPSCs possess a fibroblast-like morphology, retaining characteristics of adult multipotent stem cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 40 publications
(104 reference statements)
1
59
0
13
Order By: Relevance
“…This kind of behavior can also be observed for other cells, like pluripotent stem cells (PSC). For PSC culture, the presence of feeder cells on the first days of culture seems to be essential (Takahashi et al 2007), since just after some weeks it is possible to keep the cells feederfree, but using media supplemented with exogenous factors (Beltrão-Braga et al 2011). Finally, our data revealed similar results for all cultures conditions without feeder layer contact, leading to cell death approximately after 1 week in culture.…”
Section: Discussionsupporting
confidence: 75%
“…This kind of behavior can also be observed for other cells, like pluripotent stem cells (PSC). For PSC culture, the presence of feeder cells on the first days of culture seems to be essential (Takahashi et al 2007), since just after some weeks it is possible to keep the cells feederfree, but using media supplemented with exogenous factors (Beltrão-Braga et al 2011). Finally, our data revealed similar results for all cultures conditions without feeder layer contact, leading to cell death approximately after 1 week in culture.…”
Section: Discussionsupporting
confidence: 75%
“…Ludwig et al (28) established a simple serum-free, animal product-free medium to support the derivation and long-term feeder-independent culture of human ESCs, which was used in the present study. Sun et al (21) generated human iPSCs from adult human adipose stem cells, and Beltrão-Braga et al (29) subsequently derived iPSCs from human immature dental pulp stem cells without feeder cells. Recently, Macarthur et al (30) suggested that human neonatal fibroblast cells were able to be reprogrammed by transcription factors using a xeno-free culture system.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…В ряде работ была продемонстрирована возмож-ность индукции высокой плюрипотентности и пла-стичности СК из незрелой пульпы зуба человека (третий моляр или зуб мудрости) [36].…”
Section: развитие и претворение в жизнь концепции пластичности ск в сunclassified